Childhood trauma & resilience : a practical guide - Forkey, Heather C.; Griffin, Jessica L.; Szilagyi, Moira (American Academy of Pediatrics, 2021)
Trauma-informed care is emerging as a critical component of pediatric best practices. With this new practical guide, pediatricians and other child health professionals will learn to identify, evaluate, and treat children and families affected by trauma and adversity when they present at the office.